Designing An SKU Counter for Calculating SKU Assemblies In Warehousing: A Technology-Based Approach - Feby Gusti Dendra; Agnes Vicky; Febriza Imansuri (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
Inventory management in warehouses faces challenges in terms of SKU (Stock Keeping Unit) counting accuracy, especially in the assembly process. The manual method used is not only time-consuming but also increases the risk of recording errors, which impacts overall operational performance. This study aims to design a technology-based SKU counter (Counting System) system to improve the efficiency and accuracy of assembly SKU counting. The system is designed with a warehouse technology approach that utilizes software to automatically count assembly SKUs and generate real-time inventory reports. Implementation is carried out through simulations in a warehouse environment to test aspects of speed and accuracy. The results show that the system is able to increase operational efficiency by up to 50%, optimize the inventory management process and significantly reduce recording errors in managing assembly SKUs in the warehouse.